Age of the oldest child and internal migration of immigrant families: A study using administrative data from immigrant landing and tax files. Issue 4 (6th November 2020) - Choi, Kate H.; Ramaj, Sagi; Haan, Michael
Abstract: Immigrant parents report better opportunities for their children as the rationale for moving internationally. Residential mobility is associated with poorer outcomes for school‐age children. Many immigrant families prioritise child opportunities in their mobility decisions, especially those with school‐age children. These families may refrain from moving within the destination country to avoid such outcomes. Whether or not this is true is unknown because researchers have not examined how children's age shapes immigrant families' decisions to move within the host country. We link administrative immigration and income tax files with census data to examine how the age of the oldest child influences immigrant families' decisions to move after they immigrate. Immigrant families with school‐age children are less likely to move than those with younger children. Although the presence of older children deters migration for all immigrant families, those in immigrant gateways are more likely to move relative to those living in nongateways.